Patients With Knee Osteoarthritis Who Score Highly on the PainDETECT Questionnaire Present With Multimodality Hyperalgesia, Increased Pain, and Impaired Physical Function. Issue 1 (January 2018) - Moss, Penny; Benson, Heather A.E.; Will, Rob; Wright, Anthony
Abstract : Objectives: PainDETECT is a self-report questionnaire that can be used to identify features of neuropathic pain. A proportion of patients with knee osteoarthritis (OA) score highly on the PainDETECT questionnaire. This study aimed to determine whether those with a higher "positive neuropathic" score on the PainDETECT questionnaire also had greater pain, hypersensitivity, and reduced function compared with individuals with knee OA with lower PainDETECT scores. Materials and Methods: In total, 130 participants with knee OA completed the PainDETECT, Western Ontario and McMaster Universities Arthritis Index (WOMAC), and Pain Quality Assessment Scale questionnaires. Quantitative sensory testing was carried out at 3 sites (both knees and elbow) using standard methods. Cold and heat pain thresholds were tested using a Peltier thermode and pressure pain thresholds using a digital algometer. Physical function was assessed using 3 timed locomotor function tests. Results: In total, 22.3% of participants scored in the "positive neuropathic" category with a further 35.4% in the unclear category. Participants in the "positive neuropathic" category reported higher levels of pain and more impaired function based on the WOMAC questionnaire ( P <0.0001). They also exhibited increased levels of hyperalgesia at the knee and upper limb sites for all stimulation modalities except heat pain thresholds at the OA knee. They were also slower to complete 2 of the locomotion tasks. Discussion: This study identified a specific subgroup of people with knee OA who exhibited PainDETECT scores in the "positive neuropathic" category. These individuals experienced increased levels of pain, widespread, multimodality hyperalgesia, and greater functional impairment than the remaining cohort. Identification of OA patients with this pain phenotype may permit more targeted and effective pain management.